If I Can't Have You - Morrison, Mary B. (New York, NY : Dafina Books/Kensington Publishing Corp., 2015)
The owner of a multimillion-dollar multimedia firm, Madison Tyler enjoys her no-strings attached relationship with Granville Washington, but when she tries to break things off, he refuses to let her go and will do whatever it takes to make her see that he is the perfect man for her.
Keywords: African American women -- Fiction; African American businesspeople -- Fiction; Man-woman relationships -- Fiction; Houston (Tex.) -- Fiction